Parent and teacher involvement: children with emotional and behavioral disorders - Janzen, Jessica F. (Kansas State University, 2014)
The reciprocal interaction between children and their environment can affect their development. Certain environmental interactions such as problematic parent-child relationships or peer rejection in school are associated with the development of emotional and behavioral disorders. Children with emotional and behavioral disorders experience difficulties in a variety of areas including academics, social relationships, behaviors, and life outcomes. These emotional and behavioral disorders can progress or regress depending on relationships occurring within the child’s environment. Positive, healthy, and caring parent and teacher involvement in the lives of these children is an important factor. When parents and teachers become involved, especially when they work together to set mutual goals to help with success, children with emotional and behavioral disorders may see improvements in their problem behaviors, experience more successful achievement in academics, and develop in a direction that is more normative rather than problematic. This information can be applied through an online educational module for parents of children with EBD that aims to educate these parents on the avenues to and importance of involvement.
Keywords: Emotional and behavioral disorders; Parent involvement; Teacher involvement; Children; School; Environment; Individual & Family Studies (0628); Special Education (0529)